EVALUATION OF ACID LIME (CITRUS AURANTIFOLIA) VARIETIES IN LATERITIC SOIL CONDITIONS OF ANDHRA PRADESH - D, NAGARJUNA (The Journal of Research ANGRAU, 2026)
The present study was undertaken at Agricultural Research Station, Kavali during 20222024 to assess the performance of three acid lime cultivars, namely Pramalini, Balaji and PetluruSelection 1 under red lateritic soil conditions. The experimental layout followed a RandomizedBlock Design comprising seven replications for comparative evaluation. Among the tested cultivars,Petluru Selection 1 recorded superior growth (plant height 4.47 m; plant spread 4.18 m), yield (414fruits/plant; 15.71 kg/plant) and juice content (55.3%), along with higher consumer preference,indicating its suitability for lateritic soils of Andhra Pradesh.